PENERAPAN PAKAN IKAN BERBAHAN MAGOT DAN TATA KELOLA SAMPAH ORGANIK KAMPOENG OASE ONDOMOHEN SURABAYA - Solfaine, Rondius; Haryanta, Dwi; Revitriani, Marina (Universitas Mataram, 2024)
This community service program aims to enhance the potential of urban farming techniques through the cultivation of maggots and zebrafish in Kampung Oase Ondomohen, Surabaya. The partnership activities are expected to increase productivity and foster economic self-reliance among residents by developing creative agricultural enterprises in small and limited spaces. Specifically, the program seeks to address the low productivity and entrepreneurship levels within the community by introducing maggot pellet cultivation and the utilization of narrow aquatic spaces for zebrafish farming. This collaboration with higher education institutions is designed to boost economic opportunities in the area. Another key aspect of the program is to empower community groups to improve their cultivation techniques and innovate in the production of maggot pellets and zebrafish through creative farming practices. The program will be implemented with the community group in Kampung Sayur Ondomohen, Kelurahan Ketabang, Kecamatan Genteng, Surabaya, East Java. The community will receive training to enhance their knowledge of maggot pellet production and zebrafish farming through practical knowledge transfer, workshops, application of drying techniques for maggot pellets, effective pond hygiene management, and zebrafish farming in limited spaces. The partnership will be executed in three stages: site orientation, technical farming education, and workshops to improve knowledge of maggot and zebrafish farming. This will be followed by hands-on training to enhance skills and capabilities in managing maggot and zebrafish cultivation. The program also includes community mentoring, where research-based technologies are applied in real-world scenarios to foster sustainable development